The 2021 Portuguese Presidential Elections under extraordinary circumstances: Covid-19 and the rise of the radical right in Portugal - Serra-Silva, Sofia (2022)
Despite the low mobilization of citizenry, the lack of any strong electoral competition and consequently the expected re-election of the incumbent, the 2021 Portuguese Presidential elections gained particular interest for two main reasons. Firstly, this election took place in extraordinary circumstances amid the Covid-19 pandemic. At the time, Portugal was experiencing the world’s highest number of new cases and deaths per million. Secondly, this election was noted for the support obtained by the far-right candidate, unprecedented in national elections in Portugal. Thus, this article attempts to provide an overview of the main features of the presidential elections of 2021 in Portugal, namely the measures introduced to mitigate the threat of the pandemic and assure voters’ safety, the impact of the pandemic and the lockdown in the electoral campaign, the electoral results, and the rise of the radical right in Portugal and its implications.